Effects of foot orthosis on sprinting biomechanics in flat-footed individuals - Chong, Lowell Jia Yee (2018)
The purpose of this study was to investigate the effects of foot orthosis on ground reaction force variables during running and sprinting in flat-footed individuals. Ten male flat-footed sprint-based athletes were tasked to sprint on an instrumented treadmill at different speeds (5m/s, 6m/s and 7m/s) for two different foot orthosis conditions (neutral insoles and prefabricated foot orthoses). Each participant performed one trial of sprint lasting 5-7 seconds for each speed. Anterior-posterior and vertical ground reaction force variables were measured and analysed. Comfort perception of the foot orthosis was measured using a 150mm visual analogue scale after completion of all sprint trials for each foot orthosis condition. Two-way repeated measures analysis of variance was performed on ground reaction force data. Paired sample t-test was performed on the comfort perception ratings. No significant interaction effect was found between speed and foot orthosis conditions for the ground reaction force data. Prefabricated foot orthosis was found to decrease peak propulsive force and time to peak vertical force by 3.93% and 11.86% respectively. Conversely, prefabricated foot orthosis was found to increase loading rate by 32.34%. In conclusion, findings suggest that foot orthosis does not exhibit a clear beneficial effect in flat-footed individuals during sprinting.